Clinical features of Thai male lupus: An age-matched controlled study - Mongkoltanatus J. (2014)
To study the prevalence, and clinical and laboratory manifestations of male lupus, and compare these findings with their age-matched female lupus in Thai patients. The medical records of patients with diagnosed Systemic lupus erythematosus (SLE) were reviewed. The clinical and laboratory manifestations were determined. There were 37 males in 508 patients with SLE (7.3%). There was no difference in mean ± SD age and disease duration between male patients and their 74 female age-matched controls. When compared with females, male lupus patients had a significantly lower prevalence of alopecia (13.6 vs. 44.6%, P = 0.001), arthralgia (2.7 vs. 17.6%, P = 0.032), Raynaud's phenomenon (0.0 vs. 12.2%, P = 0.027), and psychosis (0.0 vs. 13.5%, P = 0.029), but they had a significantly higher prevalence of thrombocytopenia (32.4 vs. 12.2%, P = 0.019) and renal insufficiency (40.5 vs. 16.4%, P = 0.006). Our study showed several existing sex-related differences in the clinical manifestations in Thai SLE patients. © 2007 Springer-Verlag.